Identification of Orchid Plants Species in the East Tomohon Forest Area - Gabrielle Warouw; Helen Joan Lawalata; Christny Ferdina Evie Rompas; Metilistina Sasinggala; Livana Dethris Rawung (Advances in Tropical Biodiversity and Environmental Sciences, 2024)
Orchids which belong to the Orchidaceae family, are popular ornamental plants that are loved by many people. It is estimated that there are around 5,000 species of orchids in Indonesia. Orchids live in various habitats including epiphytic, terrestrial, lithophytic, and saprophytic. Environmental factors such as temperature, air humidity, soil pH, and light intensity can affect the growth, development, and spread of orchids. Tomohon City is known as one of Indonesia's largest flower producers, one of that is orchids. In the East Tomohon forest area, various types of orchids were found, but the types of orchids that grow have not been identified. The purpose of this study was to identify the types of orchids that grow in the East Tomohon forest area based on their morphology. The identification of orchid plants is done by observing the morphological characteristics of the shape of leaves, roots, stems, colors, and flower shapes in detail so that their taxonomy can be known. The research was conducted on August 5-19, 2022 using the cruising method (exploratory survey) the acquisition of data was analyzed descriptively. The results of research on Orchid Plant Species in the East Tomohon Forest Area found 192 individuals consisting of 10 orchid species, 4 species are terrestrial orchids, they are Calanthe tripilcata (18), Nervilia aragoana (13), Phaius thankervilleae (21), Vanda sp. (25), and 6 species are epiphytic orchids, they are Coelogyne asperata (16), Coelogyne pandurata (17), Cattleya sp. (21), Dendrobium crumenatum, Oncidium ornithorhynchum (18), Phalaenopsis amabilis (27).